Two Cases of Pelvic Diffuse Large B-Cell Lymphoma - Rupam Sharma MD; Arash Heidari MD; Everardo Cobos MD; Greti Petersen MD; Amin A. Ramzan MD; Rahul D. Polineni MD (SAGE Publishing, 2022)
Primary diffuse large B-cell lymphoma presenting as an extranodal site in the pelvis is rare and can mimic a gynecological malignancy. Although management for diffuse large B-cell lymphoma is standardized and curative, prognosis depends on timely diagnosis and therapy. Diagnosis can be challenging as patients lack classical symptoms of fever, night sweats, weight loss, and lymphadenopathy associated with lymphoma. A multidisciplinary approach is recommended to diagnose and treat judiciously. In this article, we present cases of 2 females who presented with pelvic masses with initial suspicion of a gynecological malignancy but were ultimately diagnosed as diffuse large B-cell lymphoma of the pelvis and managed accordingly.